Boron-vertex modification of carba-closo-dodecaborate for high-performance magnesium-ion battery electrolyte. Issue 3 (26th January 2021) - Watanabe, Mamoru; Kanazawa, Junichiro; Hamamura, Tomofumi; Shimokawa, Takumi; Miyamoto, Kazunori; Hibino, Mitsuhiro; Nakura, Kensuke; Inatomi, Yuu; Kitazawa, Yu; Uchiyama, Masanobu
Abstract : A new family of Mg salts of carba- closo -dodecaborate was developed for Mg ion battery applications. Modification at the boron vertices drastically improves the solubility without compromising the chemical and redox stability. Abstract : Further advances in magnesium ion batteries (MIBs) require the development of electrolyte solutions with highly optimized properties. Here we report the design, synthesis and electrolytic properties of a new family of Mg salts of carba- closo -dodecaborate anions (CCAs). Detailed calculations suggested that modification at the boron vertices, previously considered inappropriate for MIB electrolytes, would be effective. Experimental studies showed that simple halogenation at the 12-B vertex of CCA drastically improves the solubility in low viscosity solvents without compromising the chemical and redox stability, and the ionic conductivity reached 6.2 mS/cm. The synthesized electrolytes showed low overpotential (≤200 mV) for Mg deposition and excellent reversible magnesium deposition/stripping with high Coulombic efficiency (≥95%).